Implementation of Lean Hospital and Continuous Improvement in Reducing Outpatient Pharmacy Waiting Time - Afrianti Handayani; Aprilita Rina Yanti; Agusdini Banun (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Prescription waiting time is a key indicator of pharmacy service quality that directly influences patient satisfaction and hospital efficiency. Data from the Outpatient Pharmacy Installation of Pelabuhan Jakarta Hospital show average waiting times of 30.49 minutes for non-compounded medications and 35.93 minutes for compounded medications. Although these figures are still within national standards, they have not met the hospital’s internal targets, indicating inefficiencies that require systematic improvement.This study aimed to analyze prescription waiting times and identify waste in outpatient pharmacy services using Lean Hospital and Continuous Improvement approaches. A qualitative analytical method with a case study design was applied. Data collection involved participatory observation, in-depth interviews with key informants (head of pharmacy, pharmacists, and technicians), and document review. Analysis utilized Lean tools such as Value Stream Mapping (VSM), identification of Value Added (VA) and Non-Value Added (NVA) activities, bottleneck analysis, fishbone diagram, and Failure Mode and Effects Analysis (FMEA).The findings revealed that service processes were dominated by non-value-added activities, especially during prescription receipt, verification, packaging, and dispensing. Major wastes included waiting, motion, and overprocessing. Contributing factors were uneven staff distribution, suboptimal e-prescribing systems, incomplete prescriptions, and lack of standardized procedures. The proposed future state VSM demonstrated potential improvements in reducing waiting time and enhancing service efficiency.